Research on the influence of dynamic contact angle of mercury meniscus on the interpretation of rock pore throat radius in mercury intrusion experiments - Dai, Jinyou; Pi, Sha; Wu, Junzhe; Zhang, Yang (Frontiers in Earth Science, 2024)
Addressing the lack of measurement methods for dynamic contact angles of mercury meniscus in mercury intrusion porosimetry experiments and the unclear understanding of the impact of dynamic contact angles on the interpretation of pore throat radius in rocks, a new type of closed mercury intrusion characteristic curve (O-R curve) is constructed utilizing the withdrawal curve O and the secondary injection curve R obtained from the experiments. Based on the excellent wetting and de-wetting correlation characteristics at the equal mercury saturation points on this curve, a method for measuring the dynamic contact angles of mercury meniscus (O-R loop method) is established. Taking the Chang 63 tight oil reservoir samples from the Nanliang Oilfield in the Ordos Basin of China as an example, this method is applied to investigate the dynamic contact angles of mercury meniscus in mercury intrusion porosimetry experiments and the impact on the interpretation of pore throat radius in rocks. The results indicate that the dynamic contact angles of mercury meniscus changes significantly during the experiments, which cannot be ignored. And the smaller pore throats lead to more severe deformation of mercury meniscus, resulting in higher wetting resistance coefficients and hysteresis angles. Calculations reveal that the pore throat radius interpreted using the modified Washburn equation (which adopts dynamic contact angles) are generally larger than those interpreted using the conventional Washburn equation (which adopts static contact angles), with relative errors ranging from 12.2% to 54.7%. The smaller the pore throats, the larger the relative errors. The analysis shows that the conventional Washburn equation significantly underestimates the reservoir pore throat radius due to the neglect of the dynamic contact angle, while the modified Washburn equation provides more accurate interpretation. Overall, this research provides a method for calculating the dynamic contact angle in mercury intrusion porosimetry experiments and has important reference significance for the accurate interpretation of rock pore throat radius.